The effect of piezo-photocatalysis on enhancing the charge carrier separation in BaTiO3/KNbO3 heterostructure photocatalyst - Zhang, Yuhan; Shen, Guodong; Sheng, Cuihong; Zhang, Fan; Fan, Wei (Applied surface science, 2021)
The secondary recombination of photogenic charge carriers caused by structural defects at the interface of BaTiO3/KNbO3 heterojunction is successfully suppressed by the built-in electric field generated by the piezoelectric effect in BaTiO3 and KNbO3. BaTiO3/KNbO3 composite photocatalyst exhibits excellent degradation performance for direct lake blue 5B dye (DLB 5B) under the synergistic effect of piezocatalysis and photocatalysis. [Display omitted] •BaTiO3/KNbO3 heterostructure photocatalysts were successfully prepared for the first time.•BaTiO3/KNbO3 presented good piezo-photocatalytic activity in degrading direct lake blue 5B dye under light irradiation and ultrasonic vibration.•The synergistic effect of piezocatalysis and photocatalysis on the separation and transfer of charge carriers was proposed. In order to reduce the secondary recombination of photogenic charge carriers caused by the structural defects at the interface of traditional heterostructure photocatlysts, and the charge shielding effect of static condition on the built-in electric field in ferroelectric/piezoelectric photocatalyst, two typical piezoelectric photocatalysts, BaTiO3 and KNbO3, were successfully compounded into a series of BaTiO3/KNbO3 heterostructure photocatalysts for the first time. BaTiO3 nanoparticles with good crystallinity are uniformly distributed on the surface of KNbO3 prism to form the BaTiO3/KNbO3 heterostructure. The piezo-response force microscopy (PFM) results and piezo-photocatalytic degradation experiments stimulated by ultrasonic vibration and light irradiation show that the separation efficiency of photogenic charge carriers and degradation performance are enhanced by the synergistic effect of piezocatalysis and photocatalysis. The piezo-photocatalytic degradation efficiency of BaTiO3/KNbO3 over direct lake blue 5B dye can reach up to 93.3%. The reaction rate constant of 0.3BaTiO3/0.7KNbO3 over the target dye is 4.44 and 8.57 times higher than that of BaTiO3 and KNbO3. This work will provide a promising paradigm to degrade organic pollutants by using synergetic effect of piezocatalysis and photocatalysis, which perhaps facilitates the practical applications of piezo-photocatalytic technology in the environmental field.